Brown bear, brown bear, what do you see? - Martin Jr, Bill; Carle, Eric (New York Henry Holt and Company, 2010)
This book is combined with images of endearing animals and Bill Martin's singsong text. With the important pre-reading concepts of rhyme, rhythm, and repetition, these picture books have long been used as beginning readers.
Keywords: Tham khảo